Poundfit exercise and cardiometabolic health in women: a quasi-experimental study - Sucipto, Adi; Rahmadani , Irianti Fitri; Afriani, Yuni; Sari, Siska Puspita; Boru, Dhelsiana Rambu Desi; Nabila , Dinda Rambu; Puspaningtyas, Desty Ervira (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Poundfit is a rhythmic, music-driven aerobic exercise that integrates cardiovascular movement and strength-based activities. Despite its growing popularity, evidence regarding its effects on cardiometabolic parameters in healthy adults remains limited. Objective: This study aimed to evaluate the effects of a short-term Poundfit exercise program on blood pressure and blood glucose levels in healthy adult women. Methods: A quasi-experimental one-group pretest–posttest design was conducted among 22 women aged 19–50 years. Participants attended Poundfit exercise sessions twice weekly for two weeks, with each session lasting 60 minutes. Blood pressure and blood glucose levels were measured before and after the intervention. Pretest–posttest comparisons were analyzed using the Wilcoxon signed-rank test. Results: Following the two-week intervention, systolic and diastolic blood pressure showed slight reductions, while blood glucose levels showed a slight increase; however, none of these changes were statistically significant (p = 0.122 for systolic blood pressure, p = 0.933 for diastolic blood pressure, and p = 0.220 for blood glucose). Conclusion: A two-week Poundfit exercise program did not result in statistically significant changes in blood pressure or blood glucose levels in healthy adult women. These findings suggest that short-term Poundfit training may be insufficient to produce measurable cardiometabolic improvements in normotensive individuals, highlighting the need for longer or more intensive exercise interventions in future studies.